ХАЛҚ ДОСТОНЛАРИДАГИ БИРЛАМЧИ ВАРИАНТ МАСАЛАСИ - Сариев, С.; Гайлиева, О. (SCIENCE and SOCIETY, 2017)
The article is devoted to the analysis of manuscripts of Uzbek versions of the eposes “Malika Ayyor”and “Gulshanbog”. There have been studied the original variants and Central Asian versions at the comparative aspest and the epos in forcign and native folklore.